Pay is not everything: Differential effects of monetary and non-monetary rewards on employees' attitudes and behaviours. Issue 3 (4th December 2017) - Peluso, Alessandro M.; Innocenti, Laura; Pilati, Massimo
Abstract : Purpose: Monetary and non-monetary rewards have rarely been considered together under the HRM perspective. Despite the vast literature on HRM, there is still a lack of studies that explicitly discuss the link between the adoption of a total reward system (TRS) and employee-related outcomes. The purpose of this paper is to investigate this important issue in order to provide insights that can help organisations devise compensation strategies that are effective in sustaining employees' positive attitudes and behaviours. Design/methodology/approach: Using a survey of 1, 092 employees, the authors examine the effect of the overall TRS on three outcome variables (i.e. job satisfaction, affective commitment, and innovative behaviour at work). Furthermore, the authors examine the impact that each component of the TRS (i.e. base pay, training and development opportunities, and positive work environment) has on the dependent variables. Findings: The results confirm that the adoption of a TRS exerts a positive influence on the aforementioned outcomes. However, interesting differences emerged when looking at the individual components in the overall sample. Originality/value: This paper provides original insights into the complex relationship between TRS and the employee-related outcomes of job satisfaction, affective commitment, and innovative behaviour at work.